pH-responsive film based on starch/polyvinyl alcohol incorporated with rhoeo discolor anthocyanins (Trandescantia spathacae) for monitoring filsh spoilage. - Petinglay, Rogeni Misaelle M.
Spoilage is defined as any unpalatable change in food detected by the senses. At present, various existing methods for sensing spoilage in fish are available however they are either expensive or time consuming. Thus, a pH-responsive film based on starch/polyvinyl alcohol (SP) incorporated with Rhoeo discolor (Trandescantia spathcea) anthocyanins was developed to monitor fish spoilage. Anthocyanins were extracted from Rhoeo discolor leaves using absolute ethanol as solvent. The crude Rhoeo discolor extract (RDE) was quantified using pH differential method and stability tests were performed. The total monometric anthocyanin content in Rhoeo discolor was found to be 87 mg cyanidin glucoside equivalents (CGE) per 100 grams fresh weight and stability tests showed that anthocyanins degrade when exposed to increased pH, heat, and light. Next, the pH-responsive film was fabricated by immobilizing the crude Rhoeo discolor extract into the starch/polyvinyl alcohol solution by casting/solvent evaporation method. FTIR spectra of the RDE film showed that anthocyanins were successfully immobilized into the SPVA matrix. Mechanical testing, showed that addition of RDE led to a decrease in tensile strength and increase in elongation at break in in RDE film than SPGB film. Response of the RDE films toward varied pH values and simulated fish spoilage conditions were in agreement with each other providing a visible color transition from red to dark purple to greenish brown tones.